Lima Dimensi Utama Lingkungan Bisnis Dan Relevansinya Bagi Perusahaan Di Era Digital: Sebuah Kajian Literatur - Yolanda Risma Dameria L. Tobing (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
This literature review discusses the importance of the business environment for the success and sustainability of companies, especially in the dynamic and competitive digital era. The business environment is classified into internal components (under the company's control, such as human resources) and external components, which are further divided into micro and macro. The five main environmental dimensions that companies must understand and manage are economic, social, industry, global, and technological. A positive environment creates effective communication and increases employee productivity.Rapid changes in the business environment demand that companies adapt and implement strategic measures. These measures include trend monitoring, flexible strategic planning, product/service diversification, innovation, and relationship development with stakeholders. Key capabilities that organizations and individuals must possess to face change are adaptation, organizational understanding, and collaboration. In-depth understanding and adaptability to the environment, including digital transformation, are crucial for identifying opportunities, anticipating threats, and creating a sustainable competitive advantage for the company.